2020
DOI: 10.30782/jrvm.641316
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Monochromatic Colors on Oxidant Antioxidant Balance in Broilers

Abstract: Poultry management is associated with light due to positive effects of photoreceptors on animal's growth, immunity and homeostasis. Colors influence the efficiency of poultry performance and behavior. Light-emitting diode (LED) can use for providing monochromatic light source.In this trial, two hundred Ross 308 broiler chicks were studied in four different light groups as follows; White (Control), Red (RL), green (GL) and blue (BL) during 42 trial days. At the end of the study, the serum Superoxide dismutase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These evaluations have therefore highlighted a picture difficult to decipher, above all due to the fact that it goes against what has already been reported in other studies in which was reported the effect of different shades of LED light on the antioxidant system of chickens. An example is given by the recent study conducted by Seyidoğlu et al [ 34 ] who evaluated the serum enzyme activities of GPX, SOD and CAT in Ross 308 broiler chicks exposed for the 42 days of the trial to white (control), red, green and blue LED light. This experimentation has shown the ability of green light to significantly increase all antioxidant activities; in any case, in none of the experimental groups were highlighted values of enzymatic activity lower than those calculated in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…These evaluations have therefore highlighted a picture difficult to decipher, above all due to the fact that it goes against what has already been reported in other studies in which was reported the effect of different shades of LED light on the antioxidant system of chickens. An example is given by the recent study conducted by Seyidoğlu et al [ 34 ] who evaluated the serum enzyme activities of GPX, SOD and CAT in Ross 308 broiler chicks exposed for the 42 days of the trial to white (control), red, green and blue LED light. This experimentation has shown the ability of green light to significantly increase all antioxidant activities; in any case, in none of the experimental groups were highlighted values of enzymatic activity lower than those calculated in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Abdo, et al (2017) found that blue light reduced the level of MDA, a marker of oxidative stress, and increased the activity of antioxidant enzymes SOD and CAT in chickens exposed to different light colors during heat stress. Seyidoğlu, et al (2020) reported that exposing Ross-308 broiler chicks to red light increased MDA levels; however, green light increased all antioxidant parameters more than blue light. Furthermore, a study conducted by Seo, et al (2015), found that using a short wavelength of light, such as green, blue, and bright blue, can improve the immune function of broiler chickens.…”
Section: Monochromatic Light and Broiler Physiological Response Blood...mentioning
confidence: 98%
“…Shorter wavelength LEDs such as PB and BB can be improved immune function and growth of broilers (Seo, et al, 2015) White (Control), Red (RL), green (GL) and blue (BL) Ross 308 highest MDA value in RL all antioxidant parameters were highest in GL SOD and GPx were higher in GL than BL Red light may be a stressor, but GL may be a positive stimulus for broiler development, oxidantantioxidant equilibrium, and homeostasis. (Seyidoğlu, et al, 2020) Interval (4L:2D, 4 times) illumination using red, blue, and white LED lights.…”
Section: Ross Broilers Chicksmentioning
confidence: 99%